Analisis Pembentukan dan Makna Kanji 海(umi)、活(katsu)、波(nami)、潮(shio)、港(minato) yang Mengandung Bushu Sanzui - Kadek Ivandika Aditya Dharma; Ladycia Sundayra (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2024)
This research aims to examine the formation and meaning of kanji which have the sanzui element bushu sanzui on Japanese online news sites. The data source used is primary data in the form of kanji letters on the site https://www3.nhk.or.jp/news/special/saigai/natural- disaster/natural-disaster_23.html. The method used is the library method. The data obtained was then analyzed using theory of Rikusho and theory of semantic. The results of this research obtained 18 data, but 5 data will be studied thaat is kanji 海(umi)、活(katsu)、波(nami)、潮 (shio)、港(minato). With detailed data, namely kai moji 3 data, keisei moji 2 data and all the data that has been researched contains lexical meaning. The kanji that have been researched have real meanings according to their formation.Keywords: formation, meaning, kanji, sanzui